Handbook of fruits and fruit processing - Sinha, Nirmal K. (Wiley-Blackwell, 2012)
"The processing of fruits continues to undergo rapid change. In the Handbook of Fruits and Fruit Processing, Second Edition, the editorial team has assembled over forty respected academicians and industry professionals from across the globe to create an indispensable resource on the scientific principles and technological methods for processing fruits of all types. Fruits are diverse and complex in production, storage, transport, packaging, processing and application. In a developed economy such as the United States approximately 60-70% fruits and vegetables are processed into various value added products and account for nearly a third of cash crop receipts and a fifth of agricultural exports. In emerging economies and markets there is an increasing emphasis on value added agriculture and realization about the nutritional aspects of fruits and vegetables.The second edition of the handbook on fruits and fruit processing further builds on the contents and quality of the first edition by incorporating contemporary and new scientific and technological developments that have occurred since its publication. The second edition improves, includes and expands the coverage of the subject matters to provide relevant developments in: horticultural biochemistry, microbiology (including HACCP, legal and safe microbial limits of fruit and fruit products entering world trade), sensory and flavor characteristics, nutrition, naturally present bioactive phenolics, postharvest physiology, storage, transportation and packaging, processing and preservation technologies (freezing, canning, aseptic processing, non-thermal technology, drying, etc.), and details on commodity processing including frozen fruits, canned fruit, jelly, jam and preserves, fruit juices, dried fruits and wines"-- Provided by publisher